О возможном участии мышей в передаче возбудителя лямблиоза - Науруэбаева, Э.Ч. (Вестник зоологии, 1969)
In connection with insufficient solution of the problem on possible circulation of lamblia cysts in nature the investigations were carried out on experimental cross infection of a mouse and a dog with lamblia cysts.
The results of investigations testify to the fact that mice proved to be susceptible to Lamblia canis. Puppies, in their turn, were susceptible to L. muris. That is why there are grounds to suppose that the circulation of Protozoa occurs in the nature between the above-mentioned animals, i. e. the mice and dogs can serve for each other the vectors and sources of lambliasis agent. Taking into account the data of 1. K. Padchenko, N. G. Stolyarchuk (1969) on the susceptibility of dogs to human lambliasis, it can be supposed that mice also are able to take an indirect part (through a dog) in lamblia circulation in the system man — some species of animals.